Research by autistic researchers: an “insider’s view” into autism. The autistic way of being - Lawson, Wenn (Frontiers in Psychiatry, 2025)
This paper introduces us to an increasingly popular understanding of autism, but as understood and experienced by Autistic people: the descriptive theory of Monotropism. Initially this paper sets out the background to monotropism as the author briefly mentions various autism theories and highlights some reasons why such theories didn’t resonate with Autistic people. Uncovering how monotropism explains autism and Autistic experience takes the reader into the very heart of Autistic experience in ways not previously shown. As well as discussing attention, interest and connections to the Autistic sensory experiences (external and internal) the author highlights the experience of Object Permanence (OP) and its impact upon Autistic lives. Current research is beginning to demonstrate that OP is experienced differently in Autistic lives to non-autistic lives. Initially though Autistic people were thought to relate to OP in similar ways to non-autistic people (e.g.), although there were hints that aspects of OP in Autistic people were experienced differently. The reasons for why monotropism has grown in popularity and how this theory explains the Autistic experience are set out below.